(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
Prediction of the functional role of the genetic variants in Schizophrenia (SCZ) using the bioinformatics toolkit showed that decreased levels of CPLX2 gene are associated with the rs1366116*Т allele and rs3892909*C alleles of the same gene. On the contrary, rs4940456 is not associated with changes in the CPLX4 expression level, but the other SNPs linked to it correlate with the increased expression of the LMAN1. Minor allele of rs1049171-linked SNP rs17106725*T is associated with the increased CRMP4 expression. The expression of the STK32A gene is also increased in patients with SCZ, though LD analysis did not reveal genetic variants linked to rs1049171. Thus, the carriage of rs1049171*G does not have any impact on the STK32A expression in SCZ. Finally, rs1366116 and rs3892909 of the CPLX2, rs4940456 of the CPLX4 and rs1049171 of the CRMP4 genes might be indirect markers for the gene expression changes in patients with SCZ.